Maintenance treatment in relapsed canine lymphoma after a short L-CHOP protocol - Troedson, Karin; Ignatenko, Nataliia; Fejos, Csilla; Zablotski, Yury; Hirschberger, Johannes (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2021)
Objective A number of different rescue protocols for relapsed canine multicentric large-cell lymphoma have been described. The aim of this pilot study was to evaluate the efficacy of a maintenance treatment in dogs that experienced a second complete remission after a short L-CHOP-rescue protocol.Material and methods Included in the study were dogs experiencing the first lymphoma relapse during a treatment-free period which were treated with a short L-CHOP protocol, achieved a complete remission and were afterwards treated with a continuous maintenance phase (MP) protocol. The L-CHOP protocol consisted of weekly treatments, with at least 3 additional treatments following complete remission. Thereafter the MP protocol with 2-week treatment intervals was conducted. It consisted of alternating oral home administration of different alkylating agents and one intravenously administered cytotoxic agent of a different mechanism of action. The dogs were presented either every 4 or 6 weeks for intravenous treatment and at this time a complete blood count was performed. The durations of the first remission, disease-free interval and overall survival time were evaluated.Results A total of 20 dogs were included in the study. A median of 7 weekly applications were given before the treatment was switched to the MP protocol. During MP, 14 dogs were treated intravenously every 6 weeks and 6 dogs every 4 weeks. Haematological adverse events were mainly mild. During the L-CHOP-protocol, one septic event occurred, and 2 dogs were hospitalized due to gastrointestinal adverse events. No patient required hospitalization during the MP. Fifteen dogs completed at least one cycle in the MP and a median of 8.5 chemotherapeutic treatments were administered. The median disease-free interval was 264 days and the median overall survival time was 737 days.Conclusion and clinical relevance The protocol was generally well tolerated. Since 5 patients showed disease progression during the first cycle of the MP, dogs should ideally be evaluated for minimal residual disease before being switched to the MP. The case number in the presented study was low and the treatment relatively heterogeneous. Therefore, more dogs have to be treated with the proposed protocol before general recommendations can be made.
Keywords: Chemotherapy; dog; large-cell lymphoma; multicentric lymphoma; recurrence; rescue therapy